The Effect of the Implementation of Accounting Information Systems and Information Technology on Performance in MSMEs in Palopo City - Destisa Bijak; Antong Antong; Halim Usman (PT Mattawang Mediatama Solution, 2023)
MSMEs have a very important role in the economic sector and can be considered as the backbone of the economy in Indonesia, and the strong and dynamic character of MSMEs can encourage the development of the nation's economy. This study aims to examine whether there is an influence between the application of accounting information systems and the use of information technology on the performance of MSMEs. This type of research uses quantitative. Random sampling is a data collection technique method used in this research. The sample size used is 40 SMEs. The hypothesis testing technique used is multiple linear regression and multiple coefficients of determination, which are used to measure the effect of more than one independent variable on the dependent variable through the, T test; F test. The results will show that the application of accounting information systems and the use of information technology has a positive and significant impact the performance of MSMEs